2009
DOI: 10.1063/1.3216041
|View full text |Cite
|
Sign up to set email alerts
|

Strain balanced InAs/InAsSb superlattice structures with optical emission to 10 μm

Abstract: We report the growth and optical characterization of InAsSb/InAs strain balanced superlattice structures on GaSb substrates for potential application in midinfrared photodetectors. Photoluminescence (PL) emission was observed in the range 5 μm≤λ≤10 μm at 4 K for Sb compositions 0.14≤xSb≤0.27. The PL energy was found to depend approximately linearly on antimony, consistent with a type II band lineup. The dependence of the emission energies on the Sb mole fraction is in agreement with trends predicted by various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 17 publications
1
21
0
Order By: Relevance
“…[6][7][8][9] Strain-balanced InAs/InAs 1Àx Sb x SLs have been proposed as another possible alternative to HgCdTe, 10 and have already shown great promise for mid-IR laser and photodetector structures, 11 with photoluminescence emission in the range of 5-10 lm being achieved for SL structures containing Sb concentrations of 14À27%. 12 Recently, InAs/ InAs 1Àx Sb x SLs grown by metalorganic chemical vapor depostition (MOCVD) have been studied in more detail: these SLs showed excellent structural properties and strong optical response. 13,14 The absence of gallium in these InAs/ InAs 1-x Sb x SLs is expected to simplify the SL interfaces and hence the growth process, 13 and also result in longer carrier lifetimes, 15,16 as very recently demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] Strain-balanced InAs/InAs 1Àx Sb x SLs have been proposed as another possible alternative to HgCdTe, 10 and have already shown great promise for mid-IR laser and photodetector structures, 11 with photoluminescence emission in the range of 5-10 lm being achieved for SL structures containing Sb concentrations of 14À27%. 12 Recently, InAs/ InAs 1Àx Sb x SLs grown by metalorganic chemical vapor depostition (MOCVD) have been studied in more detail: these SLs showed excellent structural properties and strong optical response. 13,14 The absence of gallium in these InAs/ InAs 1-x Sb x SLs is expected to simplify the SL interfaces and hence the growth process, 13 and also result in longer carrier lifetimes, 15,16 as very recently demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Recently, the study of another type of T2SL, namely the "Ga-free" InAs/InAsSb T2SLs grown on GaSb substrates, has been revisited and revealed very encouraging results. [12][13][14][15] Time resolved PL measurements of the InAs/InAs 0.72 Sb 0.28 T2SL structures showed minority carrier lifetimes greater than 412 ns due to strong reduction of nonradiative recombination in these superlattices. 16 Therefore, it is reasonable to expect that substantially better photodetector performance and higher operating temperature are achievable with the InAs/InAsSb T2SL materials.…”
mentioning
confidence: 99%
“…Recent studies using the type-IIb (electron well in the binary layer) alignment have found the bowing of the InAs 1Àx Sb x valence band to be between 60À70% of the bandgap bowing. 18,23,24 The calculations presented here use the type-IIb alignment with 65% of the InAs 1Àx Sb x bandgap bowing attributed to the valence band. Figure 1 displays the calculated T2SL bandgap versus the layer thicknesses for strain-balanced designs on GaSb for three different InAs 1Àx Sb x compositions.…”
Section: Modelingmentioning
confidence: 99%